Wnt/β-catenin signaling and Msx1 promote outgrowth of the maxillary prominences - Medio, Marie; Yeh, Erika; Popelut, Antoine; Babajko, Sylvie; Berdal, Ariane; Helms, Jill (Frontiers in Physiology, 2012)
Facial morphogenesis requires a series of precisely orchestrated molecular events to promote the growth and fusion of the facial prominences. Cleft palate (CP) results from perturbations in this process. The transcriptional repressor Msx1 is a key participant in these molecular events, as demonstrated by the palatal clefting phenotype observed in Msx1−/− embryos. Here, we exploited the high degree of conservation that exists in the gene regulatory networks that shape the faces of birds and mice, to gain a deeper understanding of Msx1 function in CP. Histomorphometric analyses indicated that facial development was disrupted as early as E12.5 in Msx1−/− embryos, long before the palatal shelves have formed. By mapping the expression domain of Msx1 in E11.5 and E12.5 embryos, we found the structures most affected by loss of Msx1 function were the maxillary prominences. Maxillary growth retardation was accompanied by perturbations in angiogenesis that preceded the CP phenotype. Experimental chick manipulations and in vitro assays showed that the regulation of Msx1 expression by the Wnt/β-catenin pathway is highly specific. Our data in mice and chicks indicate a conserved role for Msx1 in regulating the outgrowth of the maxillary prominences, and underscore how imbalances in Msx1 function can lead of growth disruptions that manifest as CP.